2016
DOI: 10.1016/j.physleta.2016.05.026
|View full text |Cite
|
Sign up to set email alerts
|

Stability analysis of convection in the intracluster medium

Abstract: We use the machinery usually employed for studying the onset of Rayleigh-Bénard convection in hydro-and magnetohydrodynamic settings to address the onset of convection induced by the magnetothermal instability and the heat-flux-buoyancy-driveninstability in the weakly-collisional magnetized plasma permeating the intracluster medium. Since most of the related numerical simulations consider the plasma being bounded between two 'plates' on which boundary conditions are specified, our strategy provides a framework… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 58 publications
0
12
0
Order By: Relevance
“…As far as the governing equations of motion of this system is concerned, they are the following well-known set of equations (see also Pessah & Chakraborty (2013); Gupta et al (2016)):…”
Section: Framework For Linear Stability Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…As far as the governing equations of motion of this system is concerned, they are the following well-known set of equations (see also Pessah & Chakraborty (2013); Gupta et al (2016)):…”
Section: Framework For Linear Stability Analysismentioning
confidence: 99%
“…Henceforth an infinitesimal perturbation of a physical quantity, say f , about its equilibrium state value has been denoted as δ f . Since the sound speed is much faster than the speed at which the unstable convective modes grows, it is justified to employ the Boussinesq approximation (Balbus 2000(Balbus , 2001Quataert 2008;Pessah & Chakraborty 2013;Gupta et al 2016), i.e., ∇•δu = 0. Also one has, due to the solenoidal character of the magnetic field, ∇•δB = 0.…”
Section: Framework For Linear Stability Analysismentioning
confidence: 99%
“…After the linear stability analyses of the composition gradient modified HBI and MTI have been done by Pessah & Chakraborty (2013) using the standard WKB-type approximations, Sadhukhan, Gupta & Chakraborty (2017)-following Gupta et al (2016)have shown how the problem can also be studied by employing the technique (Chandrashekhar 1981) traditionally used to study the convection problem in a Rayleigh-Bénard set-up. The latter technique has some added advantages, e.g., it connects with the boundary conditions usually adopted in the numerical simulations, it helps one to find critical Rayleigh number corresponding to the HBI and the MTI, it facilitates easier analytical estimation of the contribution from the magnetic tension, and it may help us to come up with low dimensional models for convection, like the Lorenz model (Lorenz 1963).…”
Section: Mti and Concentration Gradientmentioning
confidence: 99%
“…Out of many possible boundary conditions, we adopt the following boundary conditions (Gupta et al 2016) at the bounding plates: δu z = 0, ∂ 2 z δu z = 0, ∂ z δw z = 0, δB z = 0, ∂ z j z = 0, δθ = 0, and δc = 0. These conditions physically imply that the normal component of the velocity must be zero on the boundary surfaces, surfaces are stress-free, boundaries are perfectly conducting, the boundary surfaces are at a constant temperature, and the surfaces are at constant concentration as well.…”
Section: Mti and Concentration Gradientmentioning
confidence: 99%
See 1 more Smart Citation